Risk premium, macroeconomics shocks, and information technology: An empirical analysis - Pekka Mannonen; Elias Oikarinen (Aboa Centre for Economics (ACE), 2013)
This study identifies empirically the impact of various macroeconomic factors on the default risk premium. Using monthly data for the period 1970-2010 for the U.S., our estimations indicate that the monetary policy aggregates, risk-free interest rate, term structure of interest rates, inflation, and the state of the business cycle influence the risk premium. The results also provide some evidence in support of the hypothesis that the development of information technology has had a decreasing impact on the risk premium. Expectedly, various financial crises have had substantial and long-lasting effects on the premium. The results suggest that the direct impact of subprime crisis and Lehman collapse on the risk premium was as large as 2.5 percent-points for a sustainable period. Foreign financial crises, in turn, have lowered the risk premium in the U.S. market suggesting flight-to-safety phenomenon.
Keywords: G10; E40; E44; 330; Financial crisis; financial accelerator; external finance premium; information technology; flight-to-safety